How EFL students make requests in academic settings: Evidence from power and social distance - Khatimah, Khusnul; Nurhidayat, Nurhidayat; Noeryoko , Moechammad (Universitas Ahmad Dahlan, 2026)
This study examines the realization of request speech acts produced by English as a Foreign Language (EFL) students in academic contexts by considering variations in power and social distance. Requests constitute face-threatening acts (FTAs); therefore, their realization is strongly influenced by social and relational factors. This study employed a qualitative descriptive design supported by frequency counts and percentage distributions to quantify strategy use across situational configurations. The data were collected through a Discourse Completion Task (DCT) involving 34 undergraduate students from different semesters of the English Education Study Program at STKIP Taman Siswa Bima. The data were analysed based on request strategy classifications and mitigation devices and were interpreted through the framework of politeness theory and learner pragmatics. The findings generally indicate that conventionally indirect strategies tend to predominate in request realizations across configurations of power and social distance, though variation was observed across individual cases. In contexts characterized by asymmetrical power relations, students predominantly tended to avoid direct strategies and employed layered mitigation devices, such as apologies, politeness markers, and grounders. Meanwhile, social distance exerted a relatively consistent influence on the level of directness, as interactions with close interlocutors allowed for the use of more direct strategies. In addition, the qualitative analysis also identified recurrent patterns such as over-politeness, over-directness, and underuse of power. These tendencies are interpreted as possible reflections of local sociocultural norms and potential indications of pragmatic transfer, although pragmatic transfer was not the primary focus of the study.